2007
DOI: 10.1248/bpb.30.2141
|View full text |Cite
|
Sign up to set email alerts
|

Depigmentation of Melanocytes by Isopanduratin A and 4-Hydroxypanduratin A Isolated from <i>Kaempferia pandurata</i> R<small>OXB</small>.

Abstract: Melanin is the phenolic biopolymer that is responsible for pigmentation. Although melanin plays a crucial role in absorbing free radicals from the cytoplasm and shielding from UV light, the overproduction and accumulation of melanin in the skin could be a serious skin disorder. 1) Current therapies for skin pigmentation disease are unsatisfactory. Thus the search for natural and synthetic chemical agents to modulate the metabolism of pigmentation is of great interest. 2)Melanin biosynthesis occurs in a cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…Studies in Korea reported that two chalcone compounds, isopanduratin A and 4-hydroxypanduratin A, isolated from the ethyl acetate fraction of ethanol extract of Kaempferia pandurata exhibited inhibitory effect on melanin biosynthesis and tyrosinase activity (Yoon et al 2007 ). Compared with phenylthiourea (IC 50 = 34.3 μM) as a positive control, the depigmentation IC 50 values for isopanduratin A and 4-hydroxypanduratin A were 10.6 μM and 23.2 μM, respectively.…”
Section: Antityrosinase/skin Whitening Activitymentioning
confidence: 99%
“…Studies in Korea reported that two chalcone compounds, isopanduratin A and 4-hydroxypanduratin A, isolated from the ethyl acetate fraction of ethanol extract of Kaempferia pandurata exhibited inhibitory effect on melanin biosynthesis and tyrosinase activity (Yoon et al 2007 ). Compared with phenylthiourea (IC 50 = 34.3 μM) as a positive control, the depigmentation IC 50 values for isopanduratin A and 4-hydroxypanduratin A were 10.6 μM and 23.2 μM, respectively.…”
Section: Antityrosinase/skin Whitening Activitymentioning
confidence: 99%
“…The initial and rate-limiting step in melanin synthesis is the hydroxylation of tyrosine to dihydroxyphenylalanine or DOPA [3]. DOPAoxidation produces a highly reactive intermediate that is further oxidized to form melanin by a free radical-coupling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Email: tangkearung@yahoo.com **Kuniyoshi Shimizu, Address: Kyushu University, Fukuoka, Melanin biosynthesis occurs in a cascade of enzymatic and spontaneous reactions that convert tyrosine to melanin pigments. The initial and rate-limiting step in melanin synthesis is the hydroxylation of tyrosine to dihydroxy-phenylalanine or DOPA (Yoon et al, 2007). DOPA-oxidation produces a highly reactive intermediate that is further oxidized to form melanin by a free radical-coupling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The initial and rate-limiting step in melanin synthesis is the hydroxylation of tyrosine to dihydroxy-phenylalanine or DOPA (Yoon et al, 2007). DOPA-oxidation produces a highly reactive intermediate that is further oxidized to form melanin by a free radical-coupling pathway.…”
Section: Introductionmentioning
confidence: 99%